Analysis Of The Application For Determination Of Child Guardianship On Behalf Of The Birth Mother To Conduct The Sale Of A Plot Of Land Based On Decision Number: 235/PDT.P/2023PN.TJK - Tami Rusli; Kenny Ayu Putri (JURNAL HUKUM SEHASEN, 2024)
The purpose of this research is to understand and comprehend the considerations of the judge in granting the request for the appointment of guardianship over a child in the name of the biological mother to carry out the sale of a piece of land based on Decision Number: 235/Pdt.P/2023/PN.Tjk and to know and understand the legal consequences of the parents' position over a child who is not of sufficient age to carry out the sale of a piece of land based on Decision Number: 235/Pdt.P/2023/PN.Tjk. The research approach used in this study is a normative approach by searching and analyzing legal facts, especially those related to marriage, children, and guardianship norms in legislation, as well as conducting research on primary data in the field. The results of this study show that the judge granted the request for the appointment of guardianship based on considerations related to the child's interests, in accordance with Article 26 paragraph (1) of Law No. 35 of 2014 concerning Child Protection, which states: 'Parents are obligated and responsible for nurturing, educating, maintaining, and protecting the child.' The legal consequence of the parents' position as guardians of a minor child can be considered valid in the eyes of the law, as determined by the court.